Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s40634-021-00324-3
|View full text |Cite|
|
Sign up to set email alerts
|

Towards planning of osteotomy around the knee with quantitative inclusion of the adduction moment: a biomechanical approach

Abstract: Purpose Despite practised for decades, the planning of osteotomy around the knee, commonly using the Mikulicz-Line, is only empirically based, clinical outcome inconsistent and the target angle still controversial. A better target than the angle of frontal-plane static leg alignment might be the external frontal-plane lever arm (EFL) of the knee adduction moment. Hypothetically assessable from frontal-plane-radiograph skeleton dimensions, it might depend on the leg-alignment angle, the hip-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…A previous study on patients with a force-measuring knee implant reported significant correlations between the mediolateral load distribution and the external frontal plane lever arm (EFL), defined as the perpendicular line from the center of the knee joint to the line connecting the center of the ankle joint and the symphysis pubis. 6 These results supported the notion that the correlation between PKA and KAM peaks was higher than that between PKA and HKA before and after HTO because the concept of EFL when reflecting pelvic width is similar to PKA.…”
Section: Discussionsupporting
confidence: 80%
“…A previous study on patients with a force-measuring knee implant reported significant correlations between the mediolateral load distribution and the external frontal plane lever arm (EFL), defined as the perpendicular line from the center of the knee joint to the line connecting the center of the ankle joint and the symphysis pubis. 6 These results supported the notion that the correlation between PKA and KAM peaks was higher than that between PKA and HKA before and after HTO because the concept of EFL when reflecting pelvic width is similar to PKA.…”
Section: Discussionsupporting
confidence: 80%
“…Author details 1 Fraunhofer Institute for Biomedical Engineering IBMT, Joseph-von-Fraunhofer-Weg 1, 66280 Sulzbach, Germany. 2…”
Section: Open Accessmentioning
confidence: 99%
“…Author details 1 Fraunhofer Institute for Biomedical Engineering IBMT, Joseph-von-Fraunhofer-Weg 1, 66280 Sulzbach, Germany. 2 Charité-Universitätsmedizin Berlin, corporate member of Freie Universität Berlin, Humboldt-Universität Zu Berlin and Berlin Institute of Health, Berlin, Germany.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations